The mechanism of carcinogenesis by the neutral fraction of cigarette smoke condensate. - Roe, F; Peto, R; Kearns, F; Bishop, D (1970)
Sixteen groups, each of 50 Swiss female SPF mice, were treated thrice weekly with various combinations of 3,4-benzopyrene (BP) and/or the neutral fraction of cigarette smoke (NF) in acetone applied to the skin. Some groups received one carcinogen, some the other and some a mixture of the two. Skin tumour incidence rates were found to increase both with the dose of NF and with the dose of BP. With BP alone a threshold dose was found beyond which a very heavy incidence rate of malignant skin tumours occurred. After correction of the results for intercurrent deaths it was found that when NF and BP are applied together as a mixture they do not act independently in the production of malignant skin tumours but interact positively. This suggests that some of the components of NF act as cocarcinogens rather than as complete carcinogens. Treatment with NF appeared to increase the incidence of malignant lymphomas. The data were not suitable for deciding whether the various treatments influenced the rates of incidence of internal tumours of other types, for example, lung tumours.